The diagnostic value of the functional lumen imaging probe versus high‐resolution anorectal manometry in patients with fecal incontinence. Issue 6 (18th January 2018) - Leroi, A. M.; Melchior, C.; Charpentier, C.; Bridoux, V.; Savoye‐Collet, C.; Houivet, E.; Ducrotté, P.; Gourcerol, G.
Abstract: Background: The functional lumen imaging probe (EndoFLIP ® ) is a new technology that measures the distensibility of the anal canal represented by the anal distensibility index. The aims of this study were (i) to compare the anal distensibility index to anal pressure in a cohort of patients with fecal incontinence (FI) and (ii) to compare the diagnostic value of the EndoFLIP ® to that of high‐resolution anorectal manometry (HRAM) in the same cohort of patients. Methods: Eighty‐three consecutive patients with FI who underwent EndoFLIP ® and HRAM assessments were enrolled. The diagnostic value of the EndoFLIP ® was compared to that of HRAM and agreement between EndoFLIP ® and HRAM data was assessed. Key Results: More than 70% of the patients diagnosed with anal deficiency at rest and/or during voluntary contractions by HRAM had the same diagnosis using the EndoFLIP ® . Two patients with higher distensibility indexes at rest had normal anal resting pressures. Sixteen patients with a normal EndoFLIP ® index (ie, normal distensibility index at rest and during voluntary contractions) had an abnormal HRAM result. Seven of these 16 patients (44%) had no sphincter lesion or neuropathic disorder that could explain an abnormal anal sphincter function. Conclusions & Inferences: We demonstrated that the anal distensibility index and HRAM results are largely in agreement. We did, however, identify several discrepancies between the two techniques, indicating that they may be complementary. Abstract : The EndoFLIP ® measures the mechanical properties of the anal sphincter (ie, the distensibility index). Our goal was to compare the anal distensibility index to anal pressure in a cohort of patients with fecal incontinence. The anal distensibility indexes and anal pressures were in strong agreement at rest and during voluntary contractions. We did, however, identify several discrepancies between the two techniques, indicating that they may be complementary.